Mastering skateboarding - Welinder, Per.; Whitley, Peter (Champaign, IL : Human Kinetics, 2012)
Uses color photograph sequences to provide instruction on all the biggest skateboarding tricks, techniques, and equipment, and includes tips on building skateboards.
Includes index.
Keywords: Skateboarding